Biosorption Of Methylene Green By Pycnoporous Sanguineus : Batch And Column Studies - Chiu , Han Chen (2011)
In this study, a white rot fungus, Pycnoporous sanguineus (P. sanguineus) in immobilized cells form was used as a biosorbent for the biosorption of methylene green solution. The adsorption was studied in batch and continuous system using shake flask and a packed bed column, respectively. In the batch system, the effect of contact time (2- 12 hour), initial methylene green concentration (5 mg/L, 15 mg/L and 25 mg/L) and temperature (303 K, 313 K and 323 K), on the dye adsoprtion by the immobilized cells were investigated.